Genome-Wide Identification of Populus Malectin/Malectin-Like Domain-Containing Proteins and Expression Analyses Reveal Novel Candidates for Signaling and Regulation of Wood Development - Kumar, Vikash; Donev, Evgeniy N.; Barbut, Félix R.; Kushwah, Sunita; Mannapperuma, Chanaka; Urbancsok, János; Mellerowicz, Ewa J. (Frontiers in Plant Science, 2020)
Malectin domain (MD) is a ligand-binding protein motif of pro- and eukaryotes. It is particularly abundant in Viridiplantae, where it occurs as either a single (MD, PF11721) or tandemly duplicated domain (PF12819) called malectin-like domain (MLD). In herbaceous plants, MD- or MLD-containing proteins (MD proteins) are known to regulate development, reproduction, and resistance to various stresses. However, their functions in woody plants have not yet been studied. To unravel their potential role in wood development, we carried out genome-wide identification of MD proteins in the model tree species black cottonwood (Populus trichocarpa), and analyzed their expression and co-expression networks. P. trichocarpa had 146 MD genes assigned to 14 different clades, two of which were specific to the genus Populus. 87% of these genes were located on chromosomes, the rest being associated with scaffolds. Based on their protein domain organization, and in agreement with the exon-intron structures, the MD genes identified here could be classified into five superclades having the following domains: leucine-rich repeat (LRR)-MD-protein kinase (PK), MLD-LRR-PK, MLD-PK (CrRLK1L), MLD-LRR, and MD-Kinesin. Whereas the majority of MD genes were highly expressed in leaves, particularly under stress conditions, eighteen showed a peak of expression during secondary wall formation in the xylem and their co-expression networks suggested signaling functions in cell wall integrity, pathogen-associated molecular patterns, calcium, ROS, and hormone pathways. Thus, P. trichocarpa MD genes having different domain organizations comprise many genes with putative foliar defense functions, some of which could be specific to Populus and related species, as well as genes with potential involvement in signaling pathways in other tissues including developing wood.